Prospects and Barriers of Commercial Tomato Farming in Hilly Areas of Eastern Nepal - Wagle, Shyam Prasad (Rupantaran: A Multidisciplinary Journal, 2023)
Commercialization of agriculture has become indispensible for the supply of food and nutrients to people and income generation. Thus, this study deals with the feasibility of commercial tomato farming including the analytical study of problems related to this agricultural system in the study area. This study applied household questionnaire survey, key informant survey, focus group discussions and field observation to collect relevant primary information. Secondary data were collected from previous research journals, dissertations and official records. This study covers the entire area of Ward No. 9 of Dhankuta Municipality. The study based on around, 30 percent (280hhs) farm households of the study area. This study reveals that the commercial tomato farming in the hilly areas of eastern Nepal seems to be full of both challenges and opportunities. The commercial success of this agricultural system seems to have made this system widespread in the eastern hills of Nepal. Apart from this, it also helps to develop the habit of choosing appropriate agricultural technology among the local farmers. Thus, this farming system seems to be a more popular business at present context in this area. Moreover, this study also confirms that the commercial tomato farming is not only a profitable business but also a risky and challenging. The farmers are facing various socio-economic challenges while doing this cultivation. Therefore, this study proves that any human activity is not free from barriers or challenges, so such challenges must be faced in an intelligent way. This conclusion also conveys the message that the success achieved by facing such barriers is sustainable and fruitful.